El lenguaje del centro educativo, elemento impulsor de la igualdad de oportunidades entre géneros : la formación permanente de la comunidad educativa - Amando López Valero; Eduardo Encabo Fernández (Universidad de La Rioja, 2013)
Our societies history, has put up with a conception of them as patriarchal societies. The adrogynous model has reigned and that has caused in an important number of aspects not only women discrimination but men too. From this article, we defend the theory that one of the elements that has contributed to that discrimination, that has impregnated society has been the language. This, in his indissolubility with mind, motivates that with a bad use of it, it´s been shaped and perpetuated discriminating stereotypes. We propose working with the Educative Community for the new generations don´t be splashed by this social phenomenon, that never should have appeared because it becomes a legitimating status and power element.